Analysis of key factors influencing adaptation to e-money in transmetro Pekanbaru - Marnelly, T. Romi; Resdati, Resdati; Yesi, Yesi; Brian, Brian (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Social adaptation is an important process for individuals or groups in adjusting to new circumstances, including the adoption of technological innovations. The implementation of E-Money as a mandatory payment method in Transmetro Pekanbaru is a significant change, requiring passengers to adapt to this new system. This study aims to analyze the factors that influence passenger adaptation to E-Money using a descriptive quantitative approach. This research was conducted in Pekanbaru, with data collected through interviews with a sample of 100 respondents, which was determined from a population of 34,918 passengers using the Slovin formula with a margin of error of 10%. Data analysis was conducted to identify demographic and economic factors that influence adaptation. The results show that age, gender, occupation, income, education, private vehicle ownership, and E-Money ownership significantly affect the level of passenger adaptation to E-Money. Users who are younger, female, more educated, self-employed, or students, and who already possess E-Money tools such as Brizzi or QRIS tend to adapt more quickly. A significant finding is the dominance of QRIS and the combination of Brizzi and QRIS as preferred payment methods. However, the intensity of Transmetro usage does not significantly affect the adaptation rate. These findings suggest that strategies targeted at increasing E-Money adoption should take these demographic and socio-economic factors into account, especially by focusing on providing an accessible and user-friendly payment system for less adapted passenger groups. This study contributes to understanding the social adaptation process in the context of digital payment innovations and provides practical implications for policy makers and Transmetro Pekanbaru management in improving the effectiveness of E-Money implementation.